The Impact of the Moratory Policy on Hotel and Villa Development on Investment in Bali Tourism Development - I Nengah Pasek Suryarwan; Faisal Santiago (PT. ALHAFI BERKAH INDONESIA, 2025)
The growth of Balinese tourism has produced important notes on the impact of increasingly uncontrolled regional exploitation. Land conversion and exploitation of natural resources are of particular concern to the government. In response to this condition, the Coordinating Minister for Maritime Affairs and Investment, Luhut Binsar Panjaitan, issued a moratorium policy on hotel and villa development in Bali. The moratorium policy aims to overcome the negative impacts of over-tourism followed by the conversion of agricultural land, congestion, and environmental degradation. The problem that arises is that the moratorium policy will have an impact on uncertainty and even hinder investment plans in the tourism sector in Bali. However, this moratorium policy also encourages a shift in tourism development in the outskirts of Bali that has not been touched by tourism investment progress. The development moratorium policy is planned to be implemented in Denpasar, Badung, Gianyar, and Tabanan areas. To answer this problem, a normative legal research method is used, where the results of the research conducted are that the hotel and villa development moratorium policy in several areas of Bali will have an impact on decreasing the value of tourism investment and a negative value on local economic growth in Bali.